2022
DOI: 10.1039/d2fo02020c
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and pro-oxidant phytochemicals in ultrasound and microwave assisted extracts from hop cones: a statistical modelling approach

Abstract: The present study investigated the relationships between different green extracts from hop cones (HGEs) and their cytoprotective/cytotoxic effects on human cultured colonocytes, using a multivariate statistical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…They can also exert an important antioxidant action, particularly against the hydroperoxide radical [93]. Recently, Macchioni et al (2022) reported that ethanolic extracts from freeze-dried hop leaves exhibited a total chlorophyll content in line with the average content of green tea leaves (1.47 mg/g) [93]. In addition, the supercritical CO 2 extract from hop pellets (cv.…”
Section: Nonphenolic Pigmentsmentioning
confidence: 87%
See 2 more Smart Citations
“…They can also exert an important antioxidant action, particularly against the hydroperoxide radical [93]. Recently, Macchioni et al (2022) reported that ethanolic extracts from freeze-dried hop leaves exhibited a total chlorophyll content in line with the average content of green tea leaves (1.47 mg/g) [93]. In addition, the supercritical CO 2 extract from hop pellets (cv.…”
Section: Nonphenolic Pigmentsmentioning
confidence: 87%
“…The authors highlighted the role of the extraction process and the chosen solvent on the biological properties of hop extracts towards target cells, explaining the observed in terms of the inhibitor-promoter pair using chemometric models. The results demonstrated the crucial role of molecules such as ferulic acid (promoting)-adlupolone (inhibitor), and coumaric acid (promoting) + protocatechuic acid (inhibitor), respectively [128].…”
Section: Antitumour Activitymentioning
confidence: 92%
See 1 more Smart Citation
“…These extraction methods, including steam distillation, hydro distillation, and liquid-solvent extraction, require high temperatures, long processing times, and at times many extraction steps, limited extraction efficiency, safety issues, and environmental concerns regarding the use of toxic solvents [19][20][21][22][23][24]. Recently, green, and non-thermal alternatives such as ultrasounds, pressurized liquids, supercritical fluid extraction, pulsed electric fields, and cold plasma (CP) have been introduced to partially overcome these problems [7,[25][26][27][28]. These new methods can reduce energy consumption, process time, use of organic solvents, and loss of nutrient/nutraceutical compounds, enabling high-quality functional plant extracts [14,[29][30][31].…”
Section: Phytochemical Classmentioning
confidence: 99%
“…Medicinal and aromatic plants (MAPs) are plants or portions thereof used primarily for their medicinal or aromatic properties in pharmaceutical, nutraceutical, phytotherapeutical, cosmeceutical, etc., industries [1]. This is due to the multitude of biologically active secondary metabolites present in these plants, which allow them to be formulated into a wide range of commercial products [2], to the extent that these species are globally considered an important source of income for farmers in rural areas, fostering enormous trade from the local to the international level [3]. World trade in MAP resources is expected to grow annually at a rate of between 10 and 12%, driven by the phytotherapy sector, whose sales, according to Future Market Insights, will approach USD 500 billion by 2033, with a growth rate of around (%) over the forecast period [4].…”
Section: Introductionmentioning
confidence: 99%